Improving Employee Performance through Strengthening Transformational Leadership and Job Satisfaction in the Bogor Regency Civil Service Police Unit - Anwar, Syaiful; Yusnita , Nancy; Sunaryo, Widodo (West Science Business and Management, 2024)
The objective of this study is to examine and assess the direct and indirect impact of organizational culture and transformational leadership on the performance of Civil Service Police Unit (Satpol PP) employees in Bogor Regency, primarily through their job satisfaction. The study focuses on Satpol PP employees in the Bogor district, with a sample size of 232 individuals. Path analysis is utilized for data analysis. The findings reveal the following: (1) There is a direct positive correlation between transformational leadership and employee performance, suggesting that enhancing transformational leadership is likely to enhance employee performance. (2) Job satisfaction directly contributes to employee performance, indicating that bolstering job satisfaction is expected to improve employee performance. (3) Transformational leadership significantly influences job satisfaction, implying that strengthening leadership is likely to elevate job satisfaction levels. (4) Through both quantitative research and qualitative analysis, it is established that transformational leadership positively impacts the performance of Bogor Regency Satpol PP employees. Moreover, job satisfaction effectively acts as a mediator between transformational leadership and employee performance, indicating that enhancing both transformational leadership and job satisfaction is anticipated to enhance employee performance.